Designing a new graphite illuminator for imaging facility of INUS to improve neutron beam uniformity and intensity. (June 2019) - Nazemi, E.; Dinca, M.; Movafeghi, A.; Rokrok, B.; Dastjerdi, M.H. Choopan
Abstract: A cylindrical graphite illuminator with a thickness of 6.5 cm and diameter of 18 cm was installed inside the collimator of INUS (Instalatie de Neutronografie UScata) neutron imaging facility in the past. The graphite illuminator is usually utilized inside the collimator of neutron imaging facility to provide an intense and approximately uniform beam of neutrons at the outlet of collimator. With the mentioned existing illuminator in INUS imaging facility, the thermal neutron flux at the exit of collimator was measured 7.2 × 10 4 n/cm 2 /s. Also the obtained neutron beam profile in this facility shows that it is not completely uniform at the imaging screen and the intensity of neutrons at the top and bottom of beam profile are not the same. Hence, in this paper a new graphite illuminator is proposed to improve the neutron beam characteristics in INUS imaging facility. Monte Carlo N -Particle (MCNP) code was implemented in this study for evaluating the proposed illuminator. The shape of proposed illuminator is a cylinder whose one side is inclined. Three quality factors of thermal neutron intensity, thermal neutron beam uniformity and gamma radiation dose rate were used to evaluate performance of the new illuminator. In order to obtain optimum illuminator shape, three effective parameters of thickness, angle of inclined side and position of the illuminator inside the collimator were investigated in this research. The investigation was carried out on thicknesses in the range of 5 to 25 cm with a step of 5 cm, angles in the range of 10 to 60° with a step of 10° and positions of −5, 0 and 5 cm with respect to center of reactor core. After investigating and interpolating the results, it was found that the proposed illuminator with a thickness of 10 cm, angle of 54.5° and position of 0 can produce a uniform beam profile, increase the thermal neutron intensity up to 7.1% and also decrease the neutron to gamma ratio up to 5% in comparison with the existing one. Highlights: A new graphite illuminator is proposed to improve the neutron beam characteristics in INUS imaging facility. The shape of proposed illuminator is a cylinder whose one side is oriented. To obtain optimum illuminator shape, 3 effective parameters were investigated by MCNPX code. The results indicated that the optimum illuminator should have a thickness of 10 cm, angle of 54.5° and position of 0.